Impact of the flavonoid-induced intestinal microbiota modulation on global energy metabolism: implication for obesity - Guzmán-Quevedo, Omar; Araújo, Alana Natalícia Vasconcelos de; Romero-Juárez, Pedro A.; Costa Silva, Jordania Candice; Soria-Melgarejo, Gonzalo; Torner, Luz; de Souza Aquino, Jailane (Frontiers in Nutrition, 2026)
Evidence from the literature clearly demonstrates the beneficial effects of flavonoids on energy metabolism. Due to this, they have become important candidates for combating metabolic disorders like obesity and diabetes. Intestinal microbiota (IM) has shown similar effects on metabolic regulation, contributing to host health. Several studies have shown concomitant effects on metabolism and intestinal microbial profile in response to flavonoid-based treatments. However, the role of the bidirectional interaction between IM and flavonoids in the metabolic effects of these organic compounds is less well-established. This review discusses the effects of flavonoids on the IM in regulating energy homeostasis in metabolically relevant tissues, including skeletal muscle, liver, adipose tissue, and hypothalamus. The modulation of the gut microbiota by dietary flavonoids and vice versa is also discussed. Understanding the contribution of each actor in this interaction, as well as their mechanisms of action, can help design dietary and nutritional strategies to combat metabolic disorders, including obesity, type 2 diabetes, and dyslipidemia.